Leveraging the Potential of Argentine Cities : A Framework for Policy Action - Muzzini, Elisa; Eraso Puig, Beatriz; Anapolsky, Sebastian; Lonnberg, Tara; Mora, Viviana (Washington, DC: World Bank, 2016)
Argentina’s path to economic prosperity is through efficient, sustainable and economically thriving cities. Not only are cities a spatial concentration of people, but also they generate agglomeration economies by concentrating ideas, talent, and knowledge. Argentina is one of the most urbanized countries in Latin America, with 90 percent of Argentine people currently living in cities. Argentina’s cities are geographically and economically diverse, and its largest urban area – Metropolitan Buenos Aires – is one of Latin America’s urban giants.